Happiness - Robert Lumsden (Revista Espaço Acadêmico, 2021)
He had been sitting beside the bridge for two days when the second motorbike rider joined him. It was one of the new Hondas, a more splendid machine than his heavily-laden 99cc glorified motor scooter. He hardly glanced above the newcomer’s boots as he approached and stood beside him, watching with him the raging torrent a thousand feet below. The newcomer – who introduced himself as ‘Abe’ – whistled between his teeth.